A reading of French real estate legislation and its impact on the ownership of Algerians 1830-1897 - Saoudi, mourad (The Algerian Historical Journal, 2026)
Since its occupation of Algeria, France has encountered a reality that is contrary to its political, economic and social system, and this is due to the civilizational characteristics that characterize the Algerian people, especially its legislative and judicial system of an Islamic character. Therefore, France tried to limit the ownership of the Algerians and treated them with special treatment. In its legal systems, it called them “the people” and this is to determine the type of legislation to be adopted in their new colony in order to serve the settlement project. French legislators also sought to include Algeria’s land and people in French law as an alternative to the Islamic law that hinders it, and this Until the general perception of the mechanism of the transition of power from the Turkish character to the French and the necessity of a quick transition so that France can obtain the necessary real estate container as a first process for the stability of the army and a second process for expansion, this will lead to the dismantling of the Algerians’ ownership of their lands and the disruption of the social structure.